2000
DOI: 10.1111/j.1365-2672.2000.tb05339.x
|View full text |Cite
|
Sign up to set email alerts
|

The fate ofEscherichia colithrough water treatment and in distribution

Abstract: SUMMARY The removal of E. coli bacteria at each stage of water treatment is presented, showing how the filtration stages contribute most to reduction of bacterial numbers in the water. At treatment works without filtration stages, the emphasis is put on catchment management to limit contamination of the raw water and ensure that the numbers of viable E. coli in the source water remain low. Routine monitoring of the raw water provides data on seasonal trends in numbers of E. coli bacteria and allows effective m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Rain events have been shown to promote the leaching of faecal bacteria within soil environments, leading to direct contamination of the wider environment (McMath and Holt 2000; McGechan and Vinten 2003). This study has shown that raindrops readily disperse E. coli O157:H7 from both sheep and cattle faeces.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rain events have been shown to promote the leaching of faecal bacteria within soil environments, leading to direct contamination of the wider environment (McMath and Holt 2000; McGechan and Vinten 2003). This study has shown that raindrops readily disperse E. coli O157:H7 from both sheep and cattle faeces.…”
Section: Discussionmentioning
confidence: 99%
“…Once introduced into the environment, hydrological pathways such as overland flow and preferential flow readily facilitate the dispersal of E. coli O157:H7 and other pathogens, while leaching can lead to groundwater contamination (Chalmers et al. 2000; McMath and Holt 2000; Heinonen‐Tanski and Uusi‐Kamppa 2001; Collins and Rutherford 2004). Pathogen transport following periods of heavy rainfall is especially important in increasing the concentrations of pathogens in many watersheds (Fenlon et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation